Teaching Students to Create Independent Equations based on Solving Problems by Constructing Equations - Ravshanovich, Berdiyev Bakhodir; Davronovich, Shodiyev Rizamat (International Journal Papier Public Review, 2020)
Nowadays, the science of mathematics is advancing rapidly. Scientists are working on new examples and issues awaiting a new solution. This article focuses on teaching students to do mathematical problems independently in elementary grades using equations. The result of the study suggest that Each teacher should stimulate students in the classroom, develop children’s skills in mathematics, the ability to make equations and inequalities, and solve them independently. It allows them to solve problems independently by creating mathematics proficiency equations in upper grades.